PROFIT SHARING SYSTEM OF SQUID (Loligo sp)FISHING USING FISHING GEAR STICK HELD DIP NET LANDED AT THE OCEAN FISHING PORT BELAWAN NORTH SUMATERA PROVINCE - Alvionita, Dismiani; Hendrik, Hendrik; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research of the profit sharing system of squid fishing using fishing gear stick held dip net landed at the Ocean Fishing Port Belawan North Sumatera Provinceheld on 5 March to 22 March 2018. This study was aimed to: 1) know the employment assignment based on the position, 2) describe the system for the catch between the fisherman owner and the fisherman, and 3) the income ratio between the fisherman owner and the worker fisherman using the system for the local result Law No.16 of 1964. The method used is survey method with the determination of respondents done by stratified random sampling. The results of this study indicate that the division of tasks against the effort labor of fishing stick held dip net has been in accordance with their respective positions and profit sharing system applied in this fishing business is a system of local revenue sharing with the percentage of profit sharing 60% for the owner and 40% for fishermen laborers. Owner's income is 30 GT (IDR.60,030,000), fisherman's labor (IDR.40.020.000), and for the 40 GT fisherman owner (IDR.143.120.000), fisherman's labor (IDR.57.248.000). While using the profit-sharing system according to the Act, the income of fishermen laborers rose with the highest percentage increase of 107%. Such a far-reaching income comparison proves that the profit sharing using Law No.16 of 1964 is better than the local revenue share.Keywords:System, Profit Sharing, Revenue, Fishermen, Stick Held Dip Net